2010
DOI: 10.1002/hep.23669
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones inhibit hepatocarcinogenesis in hepatitis B virus-transgenic mice by peroxisome proliferator-activated receptor γ-independent regulation of nucleophosmin

Abstract: Antidiabetic thiazolidinediones (TZD) have in vitro antiproliferative effect in epithelial cancers, including hepatocellular carcinoma (HCC). The effective anticancer properties and the underlying molecular mechanisms of these drugs in vivo remain unclear. In addition, the primary biological target of TZD, the ligand-dependent transcription factor peroxisome proliferator-activated receptor c (PPARc), is up-regulated in HCC and seems to provide tumor-promoting responses. The aim of our study was to evaluate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
0
36
1
Order By: Relevance
“…α-glucosidase inhibitors have been reported to exert prolonged antiviral effects against the hepatitis B virus, which is the major risk factor for hepatic cancer. Galli et al demonstrated that TZD may inhibit hepatocarcinogenesis (42). The peroxisome proliferator-activated receptor-γ (PPAR-γ) ligand has been reported to inhibit colon cancer cell proliferation in vitro (43); however, TZD did Table 3 not decrease the risk of colon cancer in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…α-glucosidase inhibitors have been reported to exert prolonged antiviral effects against the hepatitis B virus, which is the major risk factor for hepatic cancer. Galli et al demonstrated that TZD may inhibit hepatocarcinogenesis (42). The peroxisome proliferator-activated receptor-γ (PPAR-γ) ligand has been reported to inhibit colon cancer cell proliferation in vitro (43); however, TZD did Table 3 not decrease the risk of colon cancer in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…In this study, we identified the PPARc downstream targets relevant to carcinogenesis, by using oligonucleotide microarray and gene ontology analysis. Among the identified targets and consistent with the major function of PPARc in HCC suppression, [7][8][9] Cbp/p300-interacting transactivator, with Glu/Asp-rich carboxy-terminal domain, 2 (CITED2) was identified as a direct effector of PPARc in HCC cells by chromatin immunoprecipitation (ChIP)-polymerase chain reaction (PCR). With the observation that CITED2 is significantly downregulated in primary HCCs compared with paired adjacent normal tissues, we further demonstrated the tumor suppressive properties of CITED2 through gain-or loss-of-CITED2 function analyses, which are at least in part mediated by the suppression of cell proliferation and inhibition of cell cycle G 1 -to-S phase transition.…”
Section: Introductionmentioning
confidence: 59%
“…6 We and others previously showed that rosiglitazone, a thiazolidinedione-class drug, inhibited hepatocarcinogenesis in vitro and in vivo by inducing cell apoptosis and cell cycle arrest. [7][8][9] However, the PPARc regulatory network and its molecular targets in liver cancer remain largely unknown. In this study, we identified the PPARc downstream targets relevant to carcinogenesis, by using oligonucleotide microarray and gene ontology analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Together with other agonists, TZDs showed beneficial therapeutic effects in oxidative stress-related diseases [59, 60]. As an example, rosiglitazone induces the antioxidant enzyme heme oxygenase 1 (HO-1) in hepatocytes [61] and pioglitazone protects against CP-induced oxidative stress in rats [60]. In response to oxidative stress, activation of PPAR γ has been reported to directly modulate the expression of several antioxidant genes.…”
Section: Discussionmentioning
confidence: 99%